Household Water Supply Strategies in Urban Bandung, Indonesia: Findings and Implications for Future Water Access Reporting - Muntalif, Barti Setiani; Nastiti, Anindrya; Roosmini, Dwina; Sudradjat, Arief; Meijerink, Sander V.; Smits, Antoine J.M. (Journal of Engineering and Technological Sciences, 2017)
Through structured interviews and statistical analyses, this study investigated access to water and strategies of 1227 vulnerable households in Bandung, Indonesia. The use of mixed water sources, household water treatment, and home storage suggest low trust in improved sources, and compromised safety and reliability of water. While official statistics suggest a high level of access to improved water sources, full-time access to such sources is overestimated. Integration of user behavior into the new monitoring approach for the water supply sector in the post-2015 development framework is proposed.